2010
DOI: 10.1103/physrevlett.104.170602
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Noise on Force Measurements

Abstract: We demonstrate how the ineluctable presence of thermal noise alters the measurement of forces acting on microscopic and nanoscopic objects. We quantify this effect exemplarily for a Brownian particle near a wall subjected to gravitational and electrostatic forces. Our results demonstrate that the force measurement process is prone to artifacts if the noise is not correctly taken into account.The concept of force plays a central role in our understanding of nature. Due to the ongoing trend towards miniaturizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
180
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(196 citation statements)
references
References 32 publications
12
180
0
Order By: Relevance
“…42 The existence of this drift velocity must be accounted for when measuring the effect of external potentials on the Brownian motion. 43 Indeed, recent experiments showed that neglecting the drift velocity leads to an erroneous qualitative evaluation of the conservative forces acting on Brownian spheres. 44 We would like to point out that the presence of a "drift" velocity does not mean that there is a net particle flux in the velocity direction.…”
Section: Spheroid Drift Velocitiesmentioning
confidence: 99%
“…42 The existence of this drift velocity must be accounted for when measuring the effect of external potentials on the Brownian motion. 43 Indeed, recent experiments showed that neglecting the drift velocity leads to an erroneous qualitative evaluation of the conservative forces acting on Brownian spheres. 44 We would like to point out that the presence of a "drift" velocity does not mean that there is a net particle flux in the velocity direction.…”
Section: Spheroid Drift Velocitiesmentioning
confidence: 99%
“…In a recent Letter [1], Volpe et al describe experiments on a colloidal particle near a wall in the presence of a gravitational field for which they study the influence of noise on the measurement of force. Their central result is a striking discrepancy between the forces derived from experimental drift measurements via their Eq.…”
mentioning
confidence: 99%
“…(1) of [1] because the nonlinearity of the diffusion coefficient enters the drift. Hence, it is impossible to derive the "force" F (z) from a measurement of the drift velocity, as in Eq.…”
mentioning
confidence: 99%
“…However, the other interpretations may also be important. For example, the experimental analysis of the colloidal particles diffusion near the boundary favours AII (λ I = 1) [44], as we have already mentioned. We performed the numerical calculations for AII, similar to those for SI, and found the same diffusion properties in respect both to the exponent and the proportionality coefficient.…”
Section: B Boundary Effects and Anomalous Diffusionmentioning
confidence: 74%
“…Emergence of the multiplicative noise near a boundary has been experimentally demonstrated for some physical systems. For example, a description of the colloidal particles diffusion in terms of a constant diffusion coefficient appears possible only if a particle remains far from any boundary [44]. Moreover, presence of the multiplicative noise in a description of particles near a wall is necessary to reach a proper thermal equilibrium [45].…”
Section: B Boundary Effects and Anomalous Diffusionmentioning
confidence: 99%